Determination of the Nutrition Standard of Soil and Leaf Analysis of Bozcaada Çavusu Grape Variety Grown in Çanakkale, Turkey - DEMIRER, TUNCAY; MUCELLA MUFTUOGLU, N.; DARDENIZ, ALPER; ORS, TULAY (Asian Journal of Chemistry, 2010)
Present study was carried out to determine the nutritional standard of Bozcaada Çavusu grape varieties, grown in Çanakkale. It was studied on the leaf blade and petiole samples, obtained from 20 vineyards on berry set stage and chosen on the soil samples, taken from 0 to 30 cm and 30 to 60 cm depth. There is no problem with pH, texture, exchangeable calcium, potassium, zinc and copper. Organic matter in all soil samples, phosphorus in 11.1 %, iron in 75 %, manganese in 50 % is inadequate. Nitrogen found was not enough in all leaf petiole sample units 60 % of leaf blade, phosphorus was found not enough in 40 % of leaf blade and in 67 % of leaf petioles. Calcium was also found at enough level in 95 % of leaf blade and in all of leaf petiole samples. The magnesium determined was not enough level in all leaf blade and 70 % of leaf petiole samples. The important negative and positive correlation, at 1 and 5 % levels, were obtained between the content of nutrient elements of soil characteristics and leaf blade and leaf petiole, according to the soil depth. On the other side, the important negative and positive correlation, at 1 and 5 % levels, were determined between the content of nutrient elements of leaf blades and leaf petioles.